Retrospective analysis of longitudinal melanonychia: A Chinese experience - Lyu, Anqi; Hou, Yinglong; Wang, Qiying (Frontiers in Pediatrics, 2023)
Objective We aimed to analyze the clinical and histopathologic characteristics of longitudinal melanonychia (LM), explore the differences between adults and children, and propose some recommendations. Methods Data on pigmentation, lentigo, subungual melanoma (SUM), and nail matrix nevus (NMN) were acquired for comparison. Results Lesions on thumbs in the children’s group were significantly fewer (p = 0.006) than in adults. Lesions on little fingers in children were more than in adults; the difference was statistically significant (p = 0.025). The widths of bands in adults were wider than in children (p < 0.001), and the duration and width were positively correlated (r = 0.474). There was more pigmentation in adults than in children; the difference was statistically significant (p = 0.005). NMN was reported in 56.1% children and 34.3% adults; the difference was statistically significant (p = 0.005). Adults had six SUM cases, whereas none in children; the difference was statistically significant (p = 0.006). The recurrence rate in adults was significantly higher than in children (p = 0.019). Conclusion The widths of bands increase with the course, indicating that LM may be progressive. The four pathological types have different distributions with age, and each type requires different treatment. The lower recurrence rate in children suggests that LM needs diagnosis and appropriate treatment as soon as possible.